Development of e-LKPD Problem Based Learning Model on Stoichiometry Material Class X Phase E SMK SMTI Padang - Hardiansyah, Hardiansyah (Universitas Negeri Padang, 2025)
This study aims to develop and test the validity and practicality of e-LKPD based on Problem Based Learning (PBL) in stoichiometry material for class X FASE E SMK SMTI Padang. The method used is the 4-D Research and Development model, limited to the Develop stage. The Data collection techniques include interviews and questionnaires. The instruments used are open-ended interview sheets (teachers) and observation questionnaires (teachers and students) in the Define stage, as well as validity questionnaires (31 items) and practicality questionnaires (12 items) in the Develop stage. The e-LKPD product was developed in the Design stage as a PBL-based digital learning medium. Validity was assessed by six validators, consisting of three chemistry lecturers from the Faculty of Mathematics and Natural Sciences, Padang State University (UNP), and three teachers of the subject Fundamentals of Industrial Chemistry Technology 6 (DDTKI 6). The practicality test involved three teachers of the subject Fundamentals of Industrial Chemistry Technology and 28 students from class X-4 TKI. Aiken's V analysis showed a value of 0.84-0.86 (valid category), and practicality received an average score of 90% from teachers and 91% from students (very practical category). This e-LKPD product is deemed suitable for use in enhancing critical thinking skills and contextual understanding of stoichiometry. Further research is recommended to test broader implementation and develop digital features based on applications to enhance flexibility and the quality of digital learning.